ANALISIS KEPUTUSAN NASABAH MENABUNG: PENDEKATAN KOMPONEN DAN MODEL LOGISTIK STUDI PADA BANK SYARIAH DI MALANG - Ghozali Maski (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2010)
The aim of this research is to analyze the Islamic banking customer preferences in Malang City. Using logistic estimation, this research found that customer decision to choose Islamic banking are influenced by variable of Islamic banking characteristic, services and trust variable, knowledge variable, and physical of bank variable. In addition, according to logistic regression coefficient, services and trust variable have the largest beta coefficient which indicated that variable had dominance variable in influencing customer preferences to save their money in Islamic banking.Keywords: Customer preferences, islamic banking, component and logistic model